Neoadjuvant TACE combined with chemo-immunotherapy for giant triple-negative breast cancer: a case report - Tan, Jie; Li, Zhuo; Li, Zhi-Jun; Kang, Feng-Lin; Xiang, Hua; Yan, Peng (Frontiers in Immunology, 2026)
Giant, ulcerated triple-negative breast cancer (TNBC) presents major therapeutic challenges. We report a 39-year-old woman with a 14.3 cm ulcerated TNBC (cT4bNxM0) who developed infection after intravenous chemotherapy. To achieve rapid local control, a multidisciplinary team elected to perform transarterial chemoembolization (TACE), followed by systemic chemo-immunotherapy using nab-paclitaxel and the PD-1 inhibitor Toripalimab. This multimodal approach led to marked tumor regression and improvement of skin ulceration, enabling curative surgery with modified radical mastectomy and complex reconstruction. Pathology postoperative showed a complete response (Miller-Payne grade 5, ypT0N0M0). This single case suggests that integrating TACE with multimodal neoadjuvant treatment sequences may be feasible in selected patients with extreme presentations of locally advanced TNBC, particularly in patients with extensive tumor burden or poor tolerance to systemic therapy. The approach may enhance local control and elicit synergistic immune activation, offering a potential paradigm for managing extreme TNBC presentations. Further studies are required to clarify the safety, efficacy, and potential immunomodulatory effects of this approach.